2020
DOI: 10.3390/cells9061513
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of SIRT6 Overexpression against DSS-Induced Colitis in Mice

Abstract: Sirtuin 6 (SIRT6), as a NAD + -dependent deacetylase, plays an indispensable role in the regulation of health and physiology. Loss of SIRT6 causes spontaneous colitis in mice and makes intestinal epithelial cells prone to stress. However, whether SIRT6 overexpression increases resistance to colitis remains unknown. Here, in vivo results demonstrated that SIRT6 overexpression attenuates DSS-induced colitis in terms of clinical manifestations, histopathological damage, loss of tight junction function and imbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Results of a previous study demonstrated that the expression of JNK in the MAPK signaling family is increased in intestinal ischemic tissues (27). Moreover, activation of TAK1-dependent NF-κB and proto-oncogene c-Jun is associated with the occurrence of intestinal inflammation and, in the case of dextran sodium sulfate-induced enteritis, the expression levels of TAK1 are significantly increased (28). These findings are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Results of a previous study demonstrated that the expression of JNK in the MAPK signaling family is increased in intestinal ischemic tissues (27). Moreover, activation of TAK1-dependent NF-κB and proto-oncogene c-Jun is associated with the occurrence of intestinal inflammation and, in the case of dextran sodium sulfate-induced enteritis, the expression levels of TAK1 are significantly increased (28). These findings are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, we did not have enough evidence to demonstrate how SIRT6 regulated p‐IκBα. It has been reported that SIRT6 may regulate phosphorylation and activation of TAK1 to inhibit NF‐κB signal‐related proteins 53 . Li et al demonstrated that SIRT6 interacted with the DNA binding domain of p65, and that this interaction decreased the occupancy of p65 at the NF‐κB target gene promoter and downregulated expression levels of p‐IκBα 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that the upregulation of SIRT6 lowered the levels of inflammatory factors TNF-a, IL-1β, and IL-6 in LPS-injured PC12 cells ( Zhaohuia and Shuiua 2020 ). SIRT6 transgenic mice showed lower levels of pro-inflammatory cytokines like TNF-a, IL-1β, and IL-6 in the dextran sulfate sodium salt (DSS)-induced colitis model than normal mice ( Xu et al, 2020 ). In addition, previous studies have reported that the SIRT6 activator UBCS039 could effectively upregulate SIRT6 and inhibit the activation of macrophages ( Zou et al, 2021 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%